Full InGaN red (625 nm) micro-LED (10 μm) demonstration on a relaxed pseudo-substrate. (3rd September 2021) - Dussaigne, Amelie; Le Maitre, Patrick; Haas, Helge; Pillet, Jean-Christophe; Barbier, Frederic; Grenier, Adeline; Michit, Nicolas; Jannaud, Audrey; Templier, Roselyne; Vaufrey, David; Rol, Fabian; Ledoux, Olivier; et al.
Abstract: The full InGaN structure was grown on two different InGaNOS substrates from Soitec. An electron blocking layer was inserted in the full InGaN light emitting diode (LED). Enhanced internal quantum efficiency of red emitting InGaN/InGaN quantum wells was measured with a value above 10% at 640 nm. 10 μ m diameter circular micro-LEDs are emitted at 625 nm with an external quantum efficiency of 0.14% at 8 A cm −2 with an estimated light extraction efficiency below 4%. With a a lattice parameter of 3.210 Å, InGaN based red LED can also emit up to 650 nm.